Evaluation and Comparison of Different Structural Systems According to Earthquake Loads - Ahmed, Sohailla Mahjoub (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
To a certain extent, the performance of seismic analysis and design requirements for a building is considered as a substantial subject amongst Civil Engineers. In general, the lateral force resisting system is the structural system that resists against lateral forces in a reinforced concrete structure while the structures are under seismic excitation. Therefore, the structural system consisting of different lateral force resisting systems, such as the shear walls, coupled shear walls and stiffened coupled shear walls are used in majority of the tall buildings. On the other hand, the tunnel formwork is one of the common structural types in regions prone to high seismic risk due to the inherent earthquake resistance of buildings. This study attempts to introduce the safest and the most economical system using different lateral force resisting structural systems of a reinforced concrete structure. These different structural systems are tested with different story levels for the purposes of predicting the safest and the most economical system. With this objective in mind, a parametric study was carried out based on the modeling of different structural systems of a reinforced concrete structure such as the flat slabbeam, the shear wall, the coupled shear wall, the stiffened coupled shear wall and the tunnel formwork system, with seven different story levels (i.e. 2, 5, 10, 15, 20, 25 and 28). These structural systems were considered as case studies that were subjected to seismic excitation loading by using the STA4-CAD software. Turkish Earthquake Code-2007 and the Turkish Standards-500 were used with a linear performance analysis method to obtain the structural design of each case study. Out of the five currently available structural systems, the flat slab-beam and the shear wall systems were proved to be appropriate for different story levels. The safest and the most economical systems were those with up to 5 stories. The tunnel formwork system was proved to be appropriate for different story levels with 10, 15, 20, 25 and 28 story levels. The analytical results of that system are in parallelism with the results of other structural systems in terms of finding the safest system. Also, the results of the tunnel formwork system indicate that as the most economical solution when compared with the total construction cost of others structural systems. Keywords: coupled shear wall, stiffened coupled shear wall, shear wall, tunnel formwork and Turkish Earthquake Code-2007

ÖZ: Deprem analizi ve tasarımı konuları inşaat mühendislerinin hep ilgisini çekmiştir. Genel olarak deprem etkilerine karşı koyması için betonarme sistemlerde çeşitli yapısal sistemler kullanılmaktadır. Bu sistemler sırasıyla perde duvar, bağ kirişli perde duvar ve güçlendirilmiş bağ kirişli perde duvar sistemleridir. Ayrıca tünel kalıp sistemleri deprem riskinin yüksek olduğu bölgelerde yüksek katlı binalar için tercih edilmektedir. Bu çalışma betonarme yapının yapısal sistemlere direnen farklı yanal kuvvetini kullanarak en güvenli ve en ekonomik sistemi tanıtmayı hedeflemektedir. Bu farklı yapı sistemleri en güvenli ve en ekonomik sistemin tahmin edilmesi amacıyla farklı kat seviyeleri ile kullanılır. Bu çalışma kapsamında betonarme çerçeve, perde duvar, bağ kirişli perde duvar, güçlendirilmiş perde duvar ile tünel kalıp yapısal sistemler yedi farklı kat sayısı için (ör. 2, 5, 10, 15, 20, 25 ve 28) karşılaştırılmıştır. Bu yapısal sistemler, STA4-CAD bilgisayar yazılımı kullanılarak sismik uyarma yüküne tabi tutulan vaka çalışmaları olarak kabul edilmiştir. Her bir vaka çalışmasının yapısal tasarımını elde etmek için doğrusal performans analizi yöntemi ile Türk Deprem Yönetmeliği 2007 ve Betonarme Yapıların Hesap Kuralları TS500 kullanılmıştır. Mevcut beş yapı sisteminden farklı kat seviyeleri için betonarme çerçeve ve perde duvar sistemlerinin uygun olduğu kanıtlanmıştır. En güvenli ve en ekonomik sistemin 5 kata kadar olanlar olduğu gözlemlenmiştir. Bu çalışmada farklı beş kat seviyesi için (10, 15, 20, 25, 28 kat) tünel kalıp sistemi kullanılmıştır. Analitik sonuçlar güvenli ve ekonomik bir yapısal sistemin sonuçlarıyla uygundur. Ayrıca, perde duvar, bağ kirişli perde duvar ve güçlendirilmiş bağ kirişli perde duvar sonuçları bu yapısal sistemlerin tünel kalıp sistemine kıyasla daha pahalı bir sonuç olduğunu göstermiştir. Anahtar Kelimeler: perde duvar, bağ kirişli perde duvar, güçlendirilmiş perde duvar, tünel kalıp, Türk Deprem Yönetmeliği 2007 (TDY-2007)
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake resistant design; Earthquake resistant design--Concrete construction--Reinforced concrete; Buildings--Earthquake effects; Reinforced concrete--Reinforced concrete construction; coupled shear wall; stiffened coupled shear wall; shear wall; tunnel formwork and Turkish Earthquake Code-2007